Basic transfer pricing - Cañete, Elsa M. (Quezon City, Philippines : Rex Printing Company, Inc., 2013)
This book explain the importance of adopting transfer pricing as a means to calculate the taxable base of income subject to tax involving transactions between related parties in both domestic and international jurisdictions.
Chapter 1: Principles of Transfer Pricing -- Chapter 2: Legal Basics of Transfer Pricing -- Chapter 3: The Arms-Length Principles -- Chapter 4: Transfer Pricing Methods -- Chapter 5: Comparability Analysis -- Chapter 6: Comparability Adjustments -- Chapter 7: Understanding Related Party Transactions -- Chapter 8: Intra-Group Services and Cost Contribution Agreement -- Chapter 9: Valuation and Taxation of Intangibles -- Chapter 10: Business Restructuring -- Chapter 11: Advance Pricing Agreement Under the Mutual Agreement Procedures (MAP APA) -- Chapter 12: Documentation -- Chapter 13: Possible Industry Issues in Transfer Pricing -- Chapter 14: Assessment of Deficiency Income Tax Arising From Transfer Pricing Adjustments.
Includes index.
Keywords: TRANSFER PRICING -- TAXATION -- LAW AND LEGISLATION